Reciprocal Learning Between Canadian and Chinese Schools Through the 24 Nature Notes Project - George Zhou; Sonia Wai-Ying Ho; Yuanrong Li; Mingyue Luo; Haley Freedman; Jian Luo (University of Windsor, 2019)
The 24 Nature Notes project was part of the China-Canada Reciprocal Learning Program. Two sister schools participated in the project. Following the same set of dates, students from both schools conducted outdoor observations and collected data. Skype meetings were arranged to exchange ideas and share student work. This study aims to understand the impact of the project on Canadian and Chinese teachers and students, what they learned from each other, and what challenges they faced. Data was collected through observation notes, meeting minutes, student work, and interviews with both Chinese and Canadian teachers and students. Data analysis revealed that the project was a positive opportunity for participants from both countries to gain cross-cultural understanding. The Canadian students enjoyed the freedom in topic selection and presentation formats. They particularly liked the life lessons that the Chinese students shared through their work. The Canadian teachers also valued the idea as it allows students to reflect their observations from a different context. The Chinese teachers and students appreciated the Canadian students' creativity. They gained inspiration from Canadian teachers and students and as a return their project work became more creative.